Effects of dosage on selected water quality parameters using moringa oleifera seed and alum - Jessica roger Tunggolou (2018)
Drinking water needs to be treated in order to satisfy the drinking water requirement according to World Health Organization. This project was aimed to compare the treatment efficiency of Moringa Oleifera seed to that of aluminum sulphate regarding their treatment efficiency. The study was conducted using Jar Tests. Data obtained from the experiments are analyzed using Microsoft Excel Office Professional Plus 2013 and Pearson Correlation using Statistical Package for the Social Sciences (SPSS). Moringa oleifera as coagulant reduced the initial turbidity reading of 30.90 ± 1.35 NTU to 3.17 ± 0.3 NTU at 150 mg/l while alum to 6.64 ± 0.92 NTU at 50 mg/l. The treatment efficiency of both coagulants are as follows; Moringa oleifera with 89% and aluminum sulphate 78%. The initial acidic groundwater pH of 5.07 ± 0.06 was raised to 6.87 ± 0.09 using Moringa oleifera while alum cause the initially acidic water to higher acidity level with 3.24 ± 0.06 being recorded as the lowest. The final conductivity of both coagulants is still within WHO standard, which is 113.33 ± 5.77 ևS/cm and 236.67 ± 11.55 ևS/cm for Moringa oleifera and alum respectively. Moringa oleifera at 150 mg/l reduced the total coliform reading from 162.00 ± 86.02 CFU/100ml to 5.00 ± 1.15 CFU/100ml while alum at 200 mg/l was reduced to 25.00 ± 2.65 CFU/100ml. The treatment efficiency for Moringa oleifera is 96% and alum 84%. For faecal coliform, the initial reading of 142.00 ± 5.51 CFU/100ml was reduced to 9.00 ± 1.53 CFU/100ml for Moringa oleifera at 450 mg/l and alum to 34.00 ± 2.52 CFU/100ml at 500 mg/l. The treatment efficiency for Moringa oleifera is 93% and alum 76%. The nutrient analysis using Moringa oleifera and alum for sulphate, initial reading of 4.00 ± 1.33 mg/l was decreased to 1.33 ± 0.58 mg/l at 50 mg/l for Moringa oleifera while alum increased to 87.00 ± 3 mg/l at the highest. For phosphate, the initial reading of 1.90 ± 0.10 mg/l decreased to 0.25 ± 0.02 mg/l at 350 mg/l for Moringa oleifera while alum decreased to 0.03 ± 0.02 mg/l at 200 mg/l. Nitrate analysis show initial reading of nitrate in the water, 2.90 ± 0.2 mg/l was reduced to 1.50 ± 0.2 mg/l at 250 mg/l for Moringa oleifera while alum decreased to 0.17 ± 0.12 mg/l at 150 mg/l. Three out of nine heavy metals analysed in this study was found to be out of the permissible limit for drinking water but however at their optimum dosage, Moringa oleifera were able to reduce the readings to being in the permitted standard for drinking water. Lead at initial reading of 0.04 ± 0.02 mg/l was reduced to 0.0015 ± 0.001 mg/l using Moringa oleifera at 200 mg/l while using alum reduced to 0.02 ± 0.005 mg/l at 250 mg/l. For iron, their initial reading of 0.45 ± 0.003 mg/l was reduced to 0.24 ± 0.002 mg/l using Moringa oleifera at 500 mg/l while using alum reduced the initial reading to 0.34 ± 0.003 mg/l at 500 mg/l. Cadmium initial concentration in the water, 0.0056 ± 0.0004 mg/l was reduced to 0.0009 ± 0.00004 mg/l using Moringa oleifera at 250 mg/l while using alum reduced the initial reading to 0.0050 ± 0.00006 mg/l at 50 mg/l.